Tolerance to salinity and dehydration in the Sahara Desert blue-eyed turtle, Mauremys leprosa saharica (Testudines: Geoemydidae) from a brackish pond in the Lower Draa basin, southern Morocco. Issue 1 (9th August 2019) - Loulida, Soumia; Znari, Mohammed; Naimi, Mohamed; Bendami, Safaa
ABSTRACT: The marginal populations of the Sahara blue-eyed pond turtle, Mauremys leprosa saharica, in the southern-most species distribution range in the pre-Saharan areas of north-west Africa, are faced with extreme environmental conditions of arid climate and anthropogenic and climate change mediated water and land salinisation. In the current study, we investigated a small and isolated population of M . l. saharica at Sidi El Mehdaoui oasis in the Lower Draa River, southern Morocco, in order to assess its osmo- and iono-regulatory abilities and tolerance to salinity and dehydration. Upon capture, turtles were weighed and measured for shell dimensions and blood and voided urine were taken. Tests of exposure to different levels of water salinity (0%, 35%, and 50% seawater) and maintenance out of water (estivation simulation) were carried out. Osmolalities and Na +, Cl −, K +, and urea concentrations were determined in plasma and voided urine, and glycaemia was measured in blood, before and after tests. Turtles were able to survive in brackish waters with a salinity as high as 24% seawater (8.4 ppt). Their voided urine was hypotonic to plasma, which indicated that they could use their bladder water reserves for osmo- and iono-regulation until the iso-osmocity level beyond which osmotic and ionic anhomeostasy can occur. Experimental tests showed that the osmo- and iono-regulatory capacities of these turtles are relatively limited, and not enough effective to allow them to survive for long-term periods in brackish/saline waters or out of water, because of dehydration indicated by progressive weight loss to a critical threshold. The increased drought, water salinisation and habitat fragmentation related to anthropogenic activities and climate change, represent great threats that can create habitats exceeding the species' threshold for a long-term persistence of the vulnerable small marginal populations of the Saharan pond turtle. So, conservation measures of these populations and their habitats are urgently needed.